Cargas não lineares no contexto da eficiência e qualidade elétrica : proposta de um protótipo - Quadros, Rodolfo (2016)
The loads with non-linear characteristics, especially electronic, has been growing steadily in the country, causing a change in the electrical system because load profile and the effects, which are of concern also increasing the scientific community. In addition to the quality aspects of electricity other issues are also current issues such as energy efficiency and billing of electricity. In this context, this work presents studies with an electronic switching device developed entitled Dimmer Flex, which allows explore the effects of electronic switching of a resistive linear load. Through studies can be analyzed holistically the impacts of the electronic switching on the measurement and hence the pricing of electricity. Studies with the prototype enable the understanding that, depending on the switching characteristics, can "become" a resistive linear load, to the measuring system, a load with inductive or capacitive behavior, thus absorbing or injecting reactive power system to which the load is connected. This finding, a priori, let’s say that switching loads electronically can influence the measurement of electric energy and, consequently, the energy bill, which reinforces the need to evaluate, discuss and to review the current metering and billing methods this input, of course, to obtain conclusive results is most necessary deepening of this subject.